Implementation of Safety Management System (SMS) for Heliport Operational Personnel at PT. Whitesky Aviation - Inka Dwi Ayu Pratiwi; Eka Prayudhista (CV. Rayyan Dwi Bharata, 2023)
Aviation safety is matters related to aviation security and safety. With the existence of a Safety Management System (SMS), airport service providers, airport transportation, or flight navigation are expected to be able to implement their operational activities as an effort to fulfill aviation safety. The heliport is where helicopters land and take off. Surface Level Heliport is a heliport located above ground level. The purpose of this study is to find out what obstacles hinder the process of implementing the Safety Management System (SMS) for heliport operational personnel at PT. Whitesky Aviation, knows the solutions that are made in overcoming problems that occur in the Safety Management System (SMS). The type of research used is descriptive qualitative research. The data collection technique used was observation in the heliport area, interviews with 3 personnel from the safety, operational, technical and documentation departments. The triangulation used is method triangulation, while the data analysis used is data reduction, data presentation, and drawing conclusions. The results of this research are the obstacles experienced during the process of implementing the Safety Management System (SMS), namely communication barriers, safety culture, and weather. In handling the constraints, the solutions taken have been very good because of the annual work program from the safety department which has been implemented and followed by all personnel in each department